Electronic transmissions and international trade - shedding new light on the moratorium debate - Andrenelli, Andrea (OECD Trade Policy Papers, 2019)
The debate about whether or not to extend the WTO Moratorium on imposing customs duties on electronic transmissions has, to date, narrowly focused on its potential customs revenue implications. This paper sets out to broaden and deepen this debate. First, by putting current estimates of the customs revenue implications into perspective, showing that potential losses tend to be low relative to overall government revenue. Second, by deepening the debate on the cost of tariffs, arguing that these are unstable sources of revenue, that they are associated with lower output and productivity and that their burden falls mainly on domestic consumers, not foreign firms. Third, by broadening the debate to consider the benefits associated with electronic transmissions, including growing consumer welfare and export competitiveness. The paper argues that, overall, the revenue implications of the Moratorium are likely to be relatively small and that its lapse would come at the expense of wider gains in the economy